Changes in Poland's housing loan market in 2004-2010 - Poskart, Robert (Zmiany na rynku kredytów mieszkaniowych w Polsce w latach 2004–2010, 2012)
The article describes changes in the mortgage market in Poland, which is a consequence of the development of real estate market started with the transition period in the 1990s. Changes in the mortgage market were very dynamic in nature, mainly due to the transformation of the macroeconomic situation and its consequences for the real estate market. After the shock caused by the credit boom in the years 2004–2007, there came another shock in the years 2008–2009 associated with the global financial crisis
Nauki o Finansach = Financial Sciences, 2012, Nr 1 (10), s. 97-115
Keywords: real estate market; mortgage loan; uncertainty; creditworthiness; rynek nieruchomości; kredyty hipoteczne; zdolność kredytowa